(untitled) (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2026)
This paper examines the key factors influencing the development of small enterprises using econometric methods, based on the case of the Andijan region. Small enterprises play a crucial role in regional economic growth by contributing to employment, production, and income generation. The study aims to identify and quantify the impact of economic and financial factors on small enterprise development through regression analysis. Statistical data covering recent years are used to construct an econometric model, where small enterprise output is considered the dependent variable, while investment volume, employment level, access to credit, and state support indicators are treated as independent variables. The results of the econometric analysis reveal significant relationships between small enterprise development and selected explanatory variables. The findings provide empirical evidence for policymakers to improve support mechanisms and create a more favorable business environment for small enterprises. The study contributes to the literature by offering a regional-level econometric assessment within an emerging economy context.